The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5402/2012/816386
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Iodine Therapy Decreases Recurrence in Thyroid Papillary Microcarcinoma

Abstract: Background. The most appropriate therapy for papillary microcarcinoma (PMC) is controversial. Methods. We reviewed the therapy and outcome of 407 patients with PMC. Results. Three hundred-eighty patients underwent total thyroidectomy, and 349 patients received I-131 therapy. The median followup was 5.3 years. Forty patients developed recurrent disease. On univariate analysis, development of disease recurrence was correlated with histological tumor size > 0.8 cm (P = 0.0104), age < 45 years (P = 0.043), and no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 40 publications
4
33
2
2
Order By: Relevance
“…RAI is usually considered based on risk assessment, however, it remains unclear whether ablative RAI is effective in reducing recurrences of small PTCs: Pelizzo et al [17] , Chow et al [18] and Creach et al [19] reported lower recurrence rates with RAI after thyroidectomy; in contrast, Baudin et al [20] , Sawka et al [21] and Schartz et al [22] failed to confirm this finding.…”
Section: Discussionmentioning
confidence: 46%
“…RAI is usually considered based on risk assessment, however, it remains unclear whether ablative RAI is effective in reducing recurrences of small PTCs: Pelizzo et al [17] , Chow et al [18] and Creach et al [19] reported lower recurrence rates with RAI after thyroidectomy; in contrast, Baudin et al [20] , Sawka et al [21] and Schartz et al [22] failed to confirm this finding.…”
Section: Discussionmentioning
confidence: 46%
“…Other studies could not find a significant correlation between multifocality and recurrent disease. 7,18,19,28 Multifocality is not a risk factor for disease recurrence in our statistical analysis, whereas the aggregate tumor size is highly significant for nodal recurrence. Ross et al 34 found similar overall recurrence rates with unifocal and multifocal PMCs; however, they also reported that patients with a multifocal disease who did not undergo a radical surgical concept (ie, total or near-total thyroidectomy) had greater rates of recurrence than patients with a similar treatment but unifocal tumors.…”
Section: Article In Pressmentioning
confidence: 77%
“…Nonetheless, it remains a matter of debate how dangerous these tumors really are and how necessary it is to take a radical approach to their treatment. 2,14,28,29 In this context the proposal to rename PMCs with a term, such as papillary microtumor, that does not include the word cancer has been suggested by various authors to improve the acceptance of less aggressive treatment. [25][26][27]30 In the literature, unfavorable outcomes are rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative 131 I therapy is used to destroy remnant thyroid tissue as well as microscopic metastases, and it affords the benefits of significant reductions in recurrence and cancer mortality rates in patients with papillary or follicular thyroid cancer [1,2]. It has also been reported that 131 I therapy improved the 5-year recurrence-free survival rates even of patients with papillary microcarcinoma [3]. Furthermore, administration of a therapeutic dose of 131 I enables visualization of persistent tumor tissue, via highly sensitive whole-body scanning, in patients with elevated levels of serum thyroglobulin [4].…”
Section: Introductionmentioning
confidence: 99%